Mechanisms of administrative empowerment and its impact on enhancing job immersion: A field study on civil protection frameworks in the state of Constantine - BENHARKATE, Hakima; BENRAMDHANE, Samia (Journal of Human Sciences, 2025)
The study aimed to analyse the impact of administrative empowerment on functional immersion in the civil protection frameworks of Constantine’s mandate, by examining the impact of delegation, training, motivation and task forces on functional immersion, preliminary data was collected through the distribution of a questionnaire to 132 civil defence frameworks (Civil Protection) of Constantine’s mandate, which included the Main Directorate, a Main Unit and two secondary units data from the human area in question were analysed through a variety of statistical processes such as descriptive analysis, Pearson coefficient, simple and multiple linear regression and variability analysis. With the statistical package SPSS issue 23, the results of the study demonstrated a positive impact of empowerment mechanisms’ reliance on identification at work and concurrent regression and relationships analysis results excluded the impact of job immersion training, The study recommended the need to strengthen proactive behaviour, value initiatives, improve incentive and remuneration systems, intensify training in digitization and improve technological assets.